Dynamical Behavior and Expressions of Solutions of a Class of Higher-Order Nonlinear Difference Equations - Ghada AlNemer; Lama Sh. Aljoufi; A. M. Ahmed; Samir Al Mohammady; M. Zakarya; H. M. Rezk (Discrete Dynamics in Nature and Society)
The aim of this article is to get the forms of the solutions of the following nonlinear higher-order difference equations χs+1=χs−3k+1/±1±Πl=1kχs−3l+1,s=0,1,2,…, where the initial conditions χ−j,j=0,1,2,…,3k−1 and k∈1,2,… are arbitrary real numbers. Also, we examine stability, boundedness, oscillation, and the periodic nature of these solutions.